Effect of olivine as MgO-bearing flux on low- and high-alumina iron ore pellets - T, Umadevi; Sah, Rameshwar (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
In the present study, the effect of MgO in the form of olivine flux on low- and high-alumina iron ore pellet mineralogy and pellet quality was studied. Green pellets were prepared by varying the MgO content from 0 to 1.5% with a basicity (CaO/SiO2) of 0.30. The pellets were tested for green pellet properties, cold crushing strength (CCS), and reduction degradation index (RDI) and fired at temperatures between 1300 and 1320 oC. An optical microscope with an image analyzer, SEM-EDS, was used to assess the mineralogical phases present in the pellets and the chemical analysis of the mineralogical phases, respectively. The laboratory tests showed that with increasing MgO addition in both low and high alumina pellets, magnesio-ferrite & silicate melt phases increased and the porosity and hematite phases decreased. The decrease in porosity was due to increase in silicate melt formation from the silica in the olivine. With increasing MgO addition, the CCS value of the pellets increased up to an MgO content of 0.9 to 1.1%. Thereafter, the CCS value of the pellets  decreased with increasing MgO addition for both low and high alumina pellets. At an MgO content of 0.9 to 1.1%, the CCS value was higher due to the formation of a low melting point magnesio-ferrite phase, which imparted strength to the pellets. For pellets with an MgO level of >1.1, the RDI was within the control limit for both low- and high-alumina pellets. This may be due to a reduction in the porosity of the pellet and a better distribution of the silicate melt phase. Low-alumina pellets showed better physical and metallurgical properties compared to high-alumina iron ore pellets.
Keywords: Iron ore pelletization, Olivine as MgO flux, low and high alumina iron ore pellets, firing, green pellet properties, mineralogy and physical & metallurgical properties